2022
DOI: 10.1155/2022/9583803
|View full text |Cite
|
Sign up to set email alerts
|

Informatization of National Public Service Fitness in Constructing a Smart City Using Big Data

Abstract: The public service system of national fitness is the condition and guarantee for the public to participate in various fitness activities. In order to effectively integrate the existing national fitness service resources and to improve the efficiency of the public service supply, this paper aims to study the informatization of building national fitness public services in smart city under the background of big data. Firstly, we build a public service information platform of national fitness in the smart city, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Literature [14] found that the most important factor in the first level of college sports openness is the hardware factor of college sports resources, and the most important factor in the second level is the spatial layout of college sports resources. Literature [15] aims to study the informatization of national fitness public service construction in smart cities under the background of big data. Combining national adaptive behavior, data mining, and support vector machine (SVM), the objective function of statistical decision-making for data mining was established.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [14] found that the most important factor in the first level of college sports openness is the hardware factor of college sports resources, and the most important factor in the second level is the spatial layout of college sports resources. Literature [15] aims to study the informatization of national fitness public service construction in smart cities under the background of big data. Combining national adaptive behavior, data mining, and support vector machine (SVM), the objective function of statistical decision-making for data mining was established.…”
Section: Introductionmentioning
confidence: 99%